Long Non-coding RNA HOTAIR Function as a Competing Endogenous RNA for miR-149-5p to Promote the Cell Growth, Migration, and Invasion in Non-small Cell Lung Cancer - Li, Hang; Cui, Zhigang; Lv, Xiaoting; Li, Juan; Gao, Min; Yang, Zitai; Bi, Yanhong; Zhang, Ziwei; Wang, Shengli; Li, Sixuan; Zhou, Baosen; Yin, Zhihua (Frontiers in Oncology, 2020)
Lung cancer is a leading cause of cancer death all around the world. Long noncoding RNAs (lncRNAs) have been confirmed to be involved in carcinogenesis of malignancies. However, the molecular mechanism of most lncRNAs in various kinds of cancers remains unclear. LncRNA HOTAIR and HNRNPA1 were reported to play an oncogenic role in non-small cell lung cancer, and the overexpression of HNRNPA1 is shown to promote the proliferation of lung adenocarcinoma cells. In our study, we found that the overexpression of HOTAIR could promote the proliferation and overexpression of miR-149-5p could inhibit the proliferation of lung cancer cells. Flow cytometric analysis determined that overexpression of miR-149-5p induced cell cycles arrest in G0/G1 phases whereas overexpression of HOTAIR decreased the proportion of G0/G1phase cells. Also, overexpression of HOTAIR promoted the migration and invasion ability of lung cancer cells, confirmed by wound healing assay and transwell assay, which was suppressed by overexpression of miR-149-5p. Furthermore, dual-luciferase reporter assay indicated that miR-149-5p could bind both HOTAIR and the 3’UTR of HNRNPA1. In summary, we found that HOTAIR can regulate HNRNPA1 expression through a ceRNA mechanism by sequester miR-149-5p which post-transcriptionally targets HNRNPA1, thus promoting lung cancer progression.